An examination of the response of ethylene-vinyl acetate film to changes in environmental conditions - Badiee, Amir (2016)
Photovoltaics are used for the direct conversion of sunlight into electricity. In order to provide useful power, the individual solar cells must be connected together. This electrically connected and environmentally protected unit is termed a photovoltaic (PV) module. The structure of a PV module consists of a number of layers of various materials with different properties. The encapsulation material is one of the critical components of a PV module. It mechanically protects the devices and electrically insulates them, ideally for at least the 20-25 year lifetime of the modules. The lifetime of a PV module is generally limited by the degradation of the constituent parts. The materials degrade and cause a decrease in the efficiency leading to eventual failure, with the encapsulant being particularly susceptible to degradation. The most common encapsulant material is Ethylene Vinyl Acetate (EVA) the degradation of which leads to a significant drop in a PV module’s efficiency, durability and lifetime. EVA undergoes chemical degradation when it is exposed to environmental factors such as elevated temperature, humidity and Ultra Violet (UV) radiation. Although numerous works have been done in this field there is still a gap in knowledge to fully understand the degradation of EVA and develop a predictive tool. This work investigates the chemical degradation of an EVA encapsulant to understand the degradation mechanisms, develop a predictive model and correlate the degradation with changes in the structure and mechanical properties.